A Limnological Evaluation of Lake Jacqueline, Portage County, Wisconsin - Roesler, Craig P. (University of Wisconsin-Stevens Point, College of Natural Resources, 1985)
A wide range of limnological and related background data was collected for Lake Jacqueline, a 39 acre lake located in Portage County, Wisconsin, to provide a basis for management decisions. Lake use limitations were due to extensive aquatic macrophyte coverage, periodic winterkills, shallow depth, a muck bottom, and small size. The surface watershed had an area of 156 acres. Soils were predominately loamy sands and sandy loams. Total watershed erosion was estimated to be 41 tons/yr by application of the Universal Soil Loss Equation. About 6 tons/yr of eroded soil reached the lake. The lake had a mean depth of 4.2 ft and a maximum depth of 12.8 ft. The water was soft with a very low conductivity (total hardness = 18 mg/1, conductivity = 31 umhos/cm; seven year open water means). Nutrient and Chlorophyll a concentrations and Secchi depth were indicative of mildly eutrophic conditions (total nitrogen = 1.07 mg/1, total phosphorus = 32 ug/1, chlorophyll a = 12 ug/1, Secchi depth = 1.6 m; seven year open water means). Moderate to severe dissolved oxygen depletion occurred in winters with long periods of deep snow cover. The average depth of lake sediment was 13.2 ft. The 829,000 yd^3 of sediment accounted for 76% of the original lake volume. The sediment had a high water content, 96.4% of wet weight, and a high organic matter content, 71% of dry weight. Moderate to high densities of aquatic macrophytes were found over 94% of the lake. Dominant species were nitella (Nitella sp.), lavender bladderwort (Utricularia resupinata), narrow ribbon leaf (Sparganium angustifolium), white water lily (Nymphaea tuberosa), and water shield (Brasenia Schreberi). Black bullheads (Ictalurus melas) dominated the fishery. Winterkills were reported during 1969, 1978, 1979, and 1982. A hydrologic and phosphorus budget was estimated for the lake. Direct precipitation and evaporation accounted for most of the lake's water input and output. Surface runoff provided only 11% of the total water input during 1981, and ground water input was insignificant. Estimated total annual phosphorus loading was 16.9 kg (0.107 g/m^2). Suggested management alternatives included watershed practices to reduce phosphorus loading, dredging, macrophyte control, and aeration. Dredging offered the best means of eliminating most lake use limitations, but its cost was probably prohibitive.